Circular RNAs as diagnostic biomarkers for gastric cancer: A comprehensive update from emerging functions to clinical significances - Xu, Chun-Yi; Zeng, Xi-Xi; Xu, Li-Feng; Liu, Ming; Zhang, Feng (Frontiers in Genetics, 2022)
The incidence and mortality of gastric cancer ranks as a fouth leading cause of cancer death worldwide, especially in East Asia. Due to the lack of specific early-stage symptoms, the majority of patients in most developing nations are diagnosed at an advanced stage. Therefore, it is urgent to find more sensitive and reliable biomarkers for gastric cancer screening and diagnosis. Circular RNAs (circRNAs), a novel type of RNAs with covalently closed loops, are becoming a latest hot spot in the field of. In recent years, a great deal of research has demonstrated that abnormal expression of circRNAs was associated with the development of gastric cancer, and suggested that circRNA might serve as a potential biomarker for gastric cancer diagnosis. In this review, we summarize the structural characteristics, formation mechanism and biological function of circRNAs, and elucidate research progress and existing problems in early screening of gastric cancer.